“LUEAD KHON KON JANG” (IN FAMILY WE TRUST) : AN ANALYSIS OF THE STATUS AND ROLE OF CHARACTERS IN THE COGNITIVE SYSTEM OF WOMEN IN DISPLACED CHINESE FAMILIES - Naijarun, Khwanchanok; Janthawong, Juthalak; Konkawalee, Phanthila (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
The purposes of this research are to analyze the status and role of Chinese women and to compare the evolution that affects Chinese women’s concept of thinking in each generation, which appears in the novel, Luead Khon Kon Jang (In Family We Trust), written by Ruthaiwan Wongsirasawat. Three characters were analyzed are Pranee Jira-Anan, Passorn Suriyaphairot and Nicha Jira-Anan who represented the 1st, 2nd and 3rd generation of Chinese women. This research utilized the qualitative methodology. A novel analysis of the story is based on Feminism theory. The research showed that the status and role of Chinese women in each generation cannot be changed since the status is something that people are born with. Thus, it sets the role of Chinese women to abide by social conditions from generation to generation. Second, the evolution that affects the concept of thinking in each generation of Chinese women began to change due to many factors such as social conditions, education and parenting. In other words, 1st generation Chinese women have been adhering and following the traditions. 2nd generation Chinese women started to demand equal rights between women and men. Lastly, 3rd generation Chinese women are confident and brave enough to speak their mind. This shows the evolution of the thinking process that women are starting to advocate for gender equality. Also, it shows the social potential that women and men are equal.